2016
DOI: 10.1103/physreve.94.051001
|View full text |Cite
|
Sign up to set email alerts
|

Emergent interparticle interactions in thermal amorphous solids

Abstract: Emergent interparticle interactions in thermal amorphous solidsGendelman, O.; Lerner, E.; Pollack, Y.G.; Procaccia, I.; Rainone, C.; Riechers, B. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Here F j (0) is 1. The displacement fields along the x and y directions produced by a single defect satisfy the following symmetry properties δx (1) (x, y) = −δx (1) (−x, y), δy (1) (x, y) = −δy (1) (x, −y).…”
Section: A Excess Energy Of a Disordered Configurationmentioning
confidence: 99%
See 2 more Smart Citations
“…Here F j (0) is 1. The displacement fields along the x and y directions produced by a single defect satisfy the following symmetry properties δx (1) (x, y) = −δx (1) (−x, y), δy (1) (x, y) = −δy (1) (x, −y).…”
Section: A Excess Energy Of a Disordered Configurationmentioning
confidence: 99%
“…Introduction: Emergent interactions arise in many microscopic theories of matter [1][2][3][4]. A paradigmatic example is the Lennard-Jones interaction that emerges as an induced dipole effect of polarizable constituents [5][6][7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…No analytical predictions about the typical scaling of the forces taking into account also subleading terms are available. Several numerical simulations have been carried out attempting to explain the observed behavior [35,38]. In particular, in [16,35] the authors showed that the deviation of the force from its leading behavior can be estimated numerically in molecular dynamics and the subleading term should be of order of the number of effective contacts δz = z − z c .…”
Section: Leading and Subleading Contributions To The Forces Near mentioning
confidence: 99%
“…The effective forces in thermal systems are determined by the momentum transferred when particles interact. Even when the bare forces are binary, the effective forces contain ternary, quaternary and higher order terms [10,11]. In order to lift the methods that were so useful at T = 0 one needs a new idea: in thermal systems the particle positions are indeed not stationary, but in glasses with large relaxation times one can determine the time-averaged positions before the onset of diffusion and much before the glass relaxes to thermodynamic equilibrium [12].…”
mentioning
confidence: 99%